A novel copper(I) sulfamate π-complex based on the 5-(allylthio)-1-(3, 5-dimethylphenyl)-1H-tetrazole ligand: Alternating-current electrochemical crystallization, DFT calculations, structural and NLO properties studies. (1st June 2018) - Slyvka, Yu.I.; Fedorchuk, A.A.; Pokhodylo, N.T.; Lis, T.; Kityk, I.V.; Mys'kiv, M.G.
Graphical abstract: A novel crystalline π-complex, [Cu I (C12 H14 N4 S)NH2 SO3 ], was grown. The complex was studied by single crystal X-ray diffraction, IR- and UV–Vis spectroscopy. The structure is considered as the first known example of a metal sulfamate coordination compound with a tetrazole ligand. Quantum chemical calculations were performed using DFT and the B3LYP functional. Effective laser operated non-linear optics are found. Abstract: Using the alternating-current electrochemical technique, the novel π-complex [Cu I ( m-dmphast )NH2 SO3 ] (1 ), based on the 5-(allylthio)-1-(3, 5-dimethylphenyl)-1 H -tetrazole ( m-dmphast ) ligand, was obtained and it was studied by single crystal X-ray diffraction as well as IR and UV–Vis spectroscopy. The structure1 should be considered as the first known example of a metal sulfamate coordination compound with a tetrazole ligand. The copper(I) ion in1 possesses a trigonal pyramidal environment, arranged from the N4 atom of the tetrazole core, the CC bond from the S-allyl group of the same m-dmphast ligand and O and N atoms of the NH2 SO3 − anions. The sulfamate anion is coordinated to the two neighboring Cu(I) ions in a bridged mode, occupying a basal plane (through the N atom) and an apical (through an O atom) position of the two neighboring metal trigonal pyramids. The bicolor coherent photoinduced treatment by a nanosecond Nd:YAG laser at a wavelength of 1064 nm caused the occurrence of charge density acentricity, which in turn favours an occurrence of second harmonic generation described by third rank polar tensors, that are usually forbidden for centrosymmerical crystals.